Sharing the burden: How the older generation should suffer its share of the cuts - Philip Booth; Corin Taylor (Institute of Economic Affairs (IEA), 2011)
A look at how cutting non-means-tested benefits and reforming state pensions could save 16bn a yearIn Sharing the burden - How the older generation should suffer its share of the cuts the IEA looks at the savings that would be made if non-means-tested benefits to older people were cut and the state pension system were reformed.Older people enjoy a privileged position at present. The non-means-tested benefits they receive have not been removed or reduced and the basic state pension is planned to increase above inflation. They also receive particularly favourable treatment in the tax system, with higher personal allowances than younger people and even a marriage allowance if one partner is over 75.This group has received special treatment by the government in its spending review - it has been left more or less exempt from spending cuts. At the same time younger people have felt the cuts through changes such as in tuition fees and child benefit. This paper shows how the government could save 16bn a year by cutting non-means-tested benefits to older people and reforming the state pension system.
Keywords: 330; Public spending; Public debt; Budget consolidation; Older people; Great Britain; Öffentliche Ausgaben; Öffentliche Schulden; Haushaltskonsolidierung; Ältere Menschen; Großbritannien